Iowa Birdline update, November 21, 1988 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1988)
Notes for the Iowa Birdline update for November 21, 1988. Highlights of the update include the many bird species that were observed on an Iowa Ornithologists' Union field trip to Saylorville Lake and Big Creek State Park. Also included were other interesting sightings were from around the state, including a Tundra Swan, Golden Eagles, a Red-shouldered Hawk, a Carolina Wren, and two immature female White-winged Scoters. Epson - sheet feed/flatbed